Increasing Green Open Space in Sumber Tani Village by Creating a Family Medicinal Plant Garden or TOGA - Syahputra, Fikry; Aulia, M. Rifky; Munthe, Melvin Boni Sebastian; Nababan, Daniel Lassio (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
TOGA is a home-cultivated plant that is efficacious as a medicine to meet the family's need for medicines. This community service is carried out through the Extended Thematic Field Work Program or KKNTD (Kuliah Kerja Nyata Tematik Diperpanjang), sponsored by Universitas Sumatera Utara. The decision to make the TOGA is following the KKNTD theme in which Sumber Tani Village, Batubara Regency is included in the Green Village Theme. The purpose of this activity is to improve and preserve the Green Open Space in Sumber Tani Village. In this activity, there are two activities namely repairing TOGA in each hamlet and planting medicinal plants. The result of this activity is the formation of TOGA starting from hamlets 1 to 8. Some repairs and replanting have been carried out on TOGA which has been damaged or is no longer growing. This program is expected to help the community's economy by reducing the cost of buying medicine and of course improving people's health as well.